Hybrid Kontrak Perbankan Syariah di Indonesia: Analisis Pendekatan Rasionalisme - Hadiat; Nurrohman (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Contemporary Islamic economics requires innovation in contract implementation to address modern challenges. This research examines the fundamental reasoning and philosophical aspects of combined contracts (hybrid) through a descriptive-analytical approach, considering both normative and doctrinal aspects of Islamic law. The study reveals that hybrid contracts are the result of juristic reasoning (ijtihad) aimed at creating adaptive financial instruments while maintaining compliance with Shariah principles. The development of these hybrid formats is conducted rationally to maximize benefits for Islamic business practitioners. Several forms of hybrid contracts that have evolved include Mudharabah Musytarakah (partnership and profit-sharing), Musyarakah Mutanaqisah (asset ownership financing), al-Musyarakah al-Muntahiyah bi al-Tamlik (gradual partnership), and al-Ijarah al-Muntahiyah bi al-Tamlik/IMBT (lease with ownership option).